Low gradient magnetic separation of magnetic nanoparticle under continuous flow: experimental study, transport mechanism and mathematical modelling - Tan, Yee Win (2022)

(untitled)
Low gradient magnetic separation (LGMS) of magnetic nanoparticles (MNP) has been proven to be one of the techniques with great potential for biomedical and environmental engineering applications. Recently, the underlying principle of particle capture by LGMS, through a process known as magnetophoresis, under the influence of hydrodynamic effect has been widely studied and illustrated. Even though the influence of hydrodynamic effect is very substantial for batch processes, its impact on LGMS operated at continuous flow condition remained largely unknown. Hence, in this study, the dynamical behavior of LGMS process operated under continuous flow (CF) was being studied in detail. Firstly, the LGMS experiments using poly(sodium 4-styrenesulfonate) (PSS)-functionalized-MNP with 44.1 nm core diameter and 245.3 nm hydrodynamic diameter (saturation magnetization = 69.48 emu/g) as modelled particle system was performed through batchwise (BW) and CF iii modes at different operating conditions, including (i) magnet arrangement, (ii) MNP concentration, and (iii) MNP solution flowrate. Here BW operation was used as a comparative study to elucidate the transport mechanism of MNP under the similar environment of CF-LGMS process, and it was found out that the convection induced by magnetophoresis is only significant at far-from-magnet region. Since the timescale for the induced convection to be effective is ~1200 seconds as observed from BW-LGMS experiments, it can be deduced that forced convection is more dominant on influencing the transport behavior of CF-LGMS (with resident time of about or less than 240 seconds). Moreover, in this study, it was found that the separation efficiency of CF-LGMS process can be boosted by the higher number of magnets, the higher MNP concentration and the lower flowrate of MNP solution. To better illustrate the underlying dynamical behavior of LGMS process, a mathematical model was developed to predict its separation efficiency and kinetic profile. The separation efficiency of CF-LGMS process was determined at great accuracy, with average error of ~2.6% compared to the experimental results. Last but not least, to verify the feasibility of implementing the CF-LGMS process to achieve sufficiently high separation efficiency in the real time application, the CF-LGMS experiments were conducted in multistage manner, which resembles the MNP solution that is flowing through a few separation columns at are connected in series. The outcome from these experiments shows that the separation efficiency (both experiment and simulation results) can be boosted to almost 90% after undergoing 3 stages of CF-LGMS column.